Effect of Heat Treatment on Microstructure and Hardness of Low Carbon Steel (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Low carbon steel is widely used in structural and engineering applications due to its excellent formability and weldability; however, its mechanical properties are highly dependent on microstructure. In the present study, the influence of different heat treatment processes on the microstructure and hardness of low carbon steel was investigated. Different heat treatment conditions, namely annealing, normalizing, conventional hardening (water quenching), Neem Bath ,Ice Bath,Salt Bath,brine Bath quenching were applied. Metallographic analysis was carried out using optical microscopy at magnifications of 100× and 500×. The results reveal significant variations in phase distribution, grain size, and morphology due to different cooling rates. Fine pearlitic structures were observed in normalized samples, whereas martensitic structures were dominant in quenched specimens. Hardness values increased with increasing cooling rate, with brine-quenched samples showing maximum hardness. The study establishes a clear correlation between heat treatment, microstructure, and hardness of low carbon steel.